2017
DOI: 10.1021/acs.langmuir.7b00030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glycosylation on Interfacial Properties of Recombinant Mucins: Adsorption, Surface Forces, and Friction

Abstract: Interfacial properties of two brush-with-anchor mucins, C-P55 and C-PSLex, have been investigated at the aqueous solution/poly(methyl methacrylate) (PMMA) interface. Both are recombinant mucin-type fusion proteins, produced by fusing the glycosylated mucin part of P-selectin glycoprotein ligand-1 (PSLG-1) to the Fc part of a mouse immunoglobulin in two different cells. They are mainly expressed as dimers upon production. Analysis of the O-glycans shows that the C-PSLex mucin has the longer and more branched si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The lubricating ability of different types of mucins has been investigated on a range of different surfaces, 28,[53][54][55][56] and the lubrication performance reported is found to vary significantly depending on the mucin used and the nature of the substrate surface. In cases where anchoring is strong and the adsorbed amount is high, low friction forces are observed due to the presence of a high density of strongly hydrated oligosaccharide chains that counteract interpenetration and facilitate hydration lubrication.…”
Section: Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The lubricating ability of different types of mucins has been investigated on a range of different surfaces, 28,[53][54][55][56] and the lubrication performance reported is found to vary significantly depending on the mucin used and the nature of the substrate surface. In cases where anchoring is strong and the adsorbed amount is high, low friction forces are observed due to the presence of a high density of strongly hydrated oligosaccharide chains that counteract interpenetration and facilitate hydration lubrication.…”
Section: Copolymersmentioning
confidence: 99%
“…53 It is generally acknowledged that it is the highly hydrated oligosaccharide side chains that facilitate lubrication between mucin layers, but only recently was it attempted to elucidate how the nature of the side-chains affects the lubrication performance between recombinant brush-with-anchor mucins. 56 It was found that the recombinant mucin with longer oligosaccharide side chains performed better at low loads, and this was interpreted as being due to higher hydration. However, at higher loads the reverse was observed and the mucin with shorter oligosaccharide side chains provided more efficient lubrication.…”
Section: Copolymersmentioning
confidence: 99%
“…With the use of contact mechanics models, the probesample contact area could now be estimated and hence an absolute quantitative frictional force could be determined. At the same time, while measuring friction with commercial AFM tips is limited to the use of silicon or silicon nitride as a material with elastic modulus >10 GPa, colloidal probes offer a greater variety of choice regarding the material chemistry, 25,26 elastic modulus <10 GPa, 27,28 and probe radius of hundreds of nanometers to few micrometers (Fig. 2).…”
Section: Evolution Of Friction Force Measurements At the Nanoscalementioning
confidence: 99%
“…The left side of the figure illustrates FFM studies using a sharp tip, either silica, [58][59][60][61][62][63][64][65][66][67][68][69][70] or silicon nitride. 32,42,68, On the right side of the figure are shown the FFM studies using a colloidal probe made from: collagen; 96 latex; 97 polyethylene (PE); 25,28,45,98 polyethylene glycol (PEG); 99 poly(methyl methacrylate) PMMA; 26,27,95,100 polystyrene (PS); 33,71,101 cellulose; 31,[102][103][104][105][106][107][108][109] and silica. 35,36,98,[110][111][112][113][114][115][116][117] The volume of the symbol corresponds to the number of studies using the specific syste...…”
Section: Effect Of Surface Interactions On Nanoscale Frictionmentioning
confidence: 99%
“…In this paper, MUC1 was chosen as an example of the mucin structure as it is most widely distributed in humans. There were several recent studies, theoretical [21][22][23], as well as experimental [24], which analyzed the docking/binding and adhesive properties of mucin, which suggest that hydrogen bonds, in particular inter-molecular interactions, play an important role in many biological processes. How mucins cross-link to form networks and which atomic interactions govern this process would seem to be of particular importance also for its frictional attributes.…”
Section: Introductionmentioning
confidence: 99%